Tuberculosis treatment experience at Hillbrow Health Centre - Makhetha, Motseng Malehloa (My University, 2008)
Tuberculosis remains a communicable disease of major public health importance in South Africa. The purpose of this study is to search for trends in management of tuberculosis at Hillbrow Health Centre from 2000 to 2002. Furthermore, to assess completeness of routine records, compare performance of tuberculosis control in this clinic with others in region 8 during 2002 and identify residential areas with high volumes of tuberculosis patients. Data was obtained from tuberculosis documents at the facility. Information provided by the district office was compared with research findings and used to evaluate performance of Hillbrow Health Centre against the other four clinics in the region. The main findings from the study conducted at Hillbrow Health Centre were the large number of patients diagnosed with tuberculosis annually and cure rates below 40% during the study period. In 2002, the clinic reported the highest proportion of TB patients and the lowest cure rate compared to the other four clinics reporting tuberculosis in region 8. “Hot spots” for the disease were identified in Hillbrow and Joubert Park suburbs and this is where Esselen, Hillbrow and Urban Health Clinics are situated. There is room for improvement of tuberculosis control. More research needs to be done to determine factors contributing to the high incidence of TB in Hillbrow and Joubert Park Suburbs.
Keywords: tuberculosis; case finding; sputum conversion rate; treatment outcomes